Combining ability analysis for yield and yield components in rice varieties of diverse origin - Vanaja, T.; Babu, Luckins C.; Radhakrishnan, V.V; Pushkaran, K. (Journal of Tropical Agriculture, 2006)
Twenty eight hybrids, produced from diallel crossing excluding reciprocals among eight parents, were studied along with the parents for combining ability for yield and 17 yield components. The study revealed importance of both additive and non-additive gene effects in governing yield and most of the yield components with preponderance of non-additive gene action for most of the yield components. Additive gene action was found important for 1000 grain weight, second uppermost internodal length and height of plant at harvest. The parent Vyttila 3 was found to be a good general combiner. The hybrids PK3355-5-1-4 x Hraswa, Vyttila 3 x IR60133-184-3-2-2, Vyttila 3 x IR36, Vyttila 3 x Mattatriveni and IR36 x Mattatriveni have shown significant favourable sca effect for yield and different yield components.